2020
DOI: 10.1158/2159-8290.cd-19-0982
|View full text |Cite
|
Sign up to set email alerts
|

Combined Cohesin–RUNX1 Deficiency Synergistically Perturbs Chromatin Looping and Causes Myelodysplastic Syndromes

Abstract: STAG2 encodes a cohesin component and is frequently mutated in myeloid neoplasms, showing highly significant co-mutation patterns with other drivers, including RUNX1. However, the molecular basis of cohesin-mutated leukemogenesis remains poorly understood. Here we show a critical role of an interplay between Stag2 and Runx1 in the regulation of enhancer-promoter looping and transcription in hematopoiesis. Combined loss of Stag2 and Runx1, which co-localize at enhancer-rich, Ctcf-deficient sites, synergisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 73 publications
4
72
0
Order By: Relevance
“…Recently, Ochi et al provided insight to this question discovering a functional relationship between STAG2 and RUNX1 in regulating chromatin structure and gene expression in hematopoietic cells. 90 The authors examined the effects of Runx1 and Stag2 double knockout in a mouse model. Interestingly, all mice that were transplanted with double knockout-derived bone marrow cells developed MDS within 6 mo, while none of the single knockout animals did, experimentally verifying that Runx1 and cohesin mutations cooperate to drive disease development.…”
Section: Mutations That Cooperate With Cohesinmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ochi et al provided insight to this question discovering a functional relationship between STAG2 and RUNX1 in regulating chromatin structure and gene expression in hematopoietic cells. 90 The authors examined the effects of Runx1 and Stag2 double knockout in a mouse model. Interestingly, all mice that were transplanted with double knockout-derived bone marrow cells developed MDS within 6 mo, while none of the single knockout animals did, experimentally verifying that Runx1 and cohesin mutations cooperate to drive disease development.…”
Section: Mutations That Cooperate With Cohesinmentioning
confidence: 99%
“…Such loops were predominantly associated with genes that exhibit a high rate of transcriptional pausing, such as p53 pathway and interferon response genes as well as some involved in ribosomal translation and DNA repair. 90 Thus, STAG2 and RUNX1 co-mutation may result in the deregulation of a specific set of genes that are critical for maintaining DNA stability and mounting an appropriate immune response to transformed cells.…”
Section: Mutations That Cooperate With Cohesinmentioning
confidence: 99%
“…The mechanism underlying clonal expansion of these driver mutations is unlikely related to defects in sister chromatid cohesion given lack of association between STAG2 mutations and complex karyotype and aneuploidy (10,18). STAG1-versus STAG2-containing complexes have been recently shown to differentially contribute to chromatin organization, facilitating longer loops at topologically associating domain (TAD) boundaries and shorter more transient nested enhancerpromoter contacts, respectively (19)(20)(21)(22). Furthermore, Stag2/Runx1 deficiency has been shown to disrupt enhancer-promoter looping and effect transcriptional pausing leading to selective gene dysregulation (22).…”
Section: Introductionmentioning
confidence: 99%
“…MDS is a clonal hematopoietic disorder characterized by bone marrow failure that can develop into acute myeloid leukemia (AML). MDS progression involves multiple signaling pathways [ 1 , 18 ]. We found that YSQHP potentially targets the apoptosis, cell cycle, p53, PI3K-AKT, and MAPK pathways in MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Myelodysplastic syndromes (MDS) are a heterogeneous group of hematological disorders characterized by bone marrow (BM) dysplasia, abnormal myeloid cell differentiation, peripheral blood cytopenia, and an increased risk of leukemic transformation [ 1 ]. MDS results in poor clinical outcomes, and the duration of patient survival is less than 2 years for the higher risk subtypes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%